67Maternal Exposure to PM2.5 from a Coal Mine Fire is Associated with Gestational Diabetes Mellitus. (2nd September 2021) - Melody, Shannon; Wills, Karen; Ford, Jane; Venn, Alison; Johnston, Fay
Abstract: Background: In 2014, the Hazelwood coal mine fire was an unprecedented six-week severe smoke event in the Latrobe Valley, southeastern Australia. We aimed to determine whether maternal exposure to fine particulate matter (PM2.5 ) attributable to coal mine fire smoke was associated with gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy and abnormal placentation. Methods: We defined a cohort of all births >20 weeks in the Latrobe Valley from 1 March 2012 - 31 Dec 2015 utilising administrative perinatal data. Average and peak PM2.5 was assigned to residential address at delivery using a chemical transport model. Maternal, meteorological and temporal variables were included in final log-binomial regression models. Results: 3, 612 singleton pregnancies were included; 766 were exposed to the smoke event. Average maternal PM2.5 exposure was 4.4 µg/m 3 (IQR 2.1). Average peak PM2.5 exposure was 44.9 µg/m 3 (IQR 35.0). An interquartile range increase in average and peak PM2.5 was associated with a 7% and 16% increased likelihood of GDM respectively (Average PM2.5 95%CI 1.03, 1.10; <0.0001; Peak PM2.5 95%CI 1.09, 1.22; <0.0001). No association for hypertensive disorders or abnormal placentation was observed. Conclusions: This is the first study to examine obstetric complications relating to a discrete smoke event. These findings may guide the public health response to future similar events. Key messages: Exposure to a smoke event was associated with an increased risk of GDM. The public health implications may be substantial with a changing climate.